Free Radical Shadow Cure Initiated Using Two-Component and Three-Component Initiator Systems - Hajime Kitano; Karthik Ramachandran; Alec B. Scranton (International Journal of Photoenergy)
In photopolymerization systems, “shadow cure” may be defined as polymerization which extends into regions which are not illuminated by the incident initiating light source. The objective of this study is to evaluate the use of fluorescent additives for polymerization in masked regions that are unilluminated by the incident initiating light. Two different fluorescent dyes are investigated: fluorescein (FL) and eosin Y spirit soluble (EYss). A systematic series of studies was performed to characterize the effects of fluorescence intensity, the incident light intensity, and the presence of a diphenyl iodonium salt on the observed degree of shadow cure. It was concluded that shadow cure may be enhanced if one or more fluorescent compounds emit fluorescent light at wavelengths absorbed by the dye in a two- or three-component photoinitiator system. The addition of DPI to the two-component systems containing MDEA and FL or EYss led to a significant enhancement in the observed shadow cure. This result was attributed to the fact that DPI will increase both the number of active centers and the mobility of the active centers as a result of the electron transfer reactions in which it participates.